Perinatal outcome in pregnant women with isolated oligohydramnios diagnosed with the single deepest pocket method - Dammer, Ulf; Pretscher, Jutta; Weiß, Christel; Schneider, Michael; Faschingbauer, Florian; Beckmann, Matthias Wilhelm; Kehl, Sven (In vivo, 2024)
Aim: The aim of this study was to investigate perinatal outcome in singleton pregnancies at term with isolated oligohydramnios, diagnosed by using the single deepest pocket method. Patients and Methods: In this historic cohort study, the perinatal outcomes of 196 women with isolated oligohydramnios at term, diagnosed by using the single deepest pocket method, were compared to 8,676 women with normal amniotic fluid volume. The primary outcome measure was the Cesarean section rate. Further outcome parameters included the rate of induction of labor, abnormal cardiotocography, umbilical cord pH and base excess, Apgar, meconium-stained liquor and admission to neonatal intensive care unit. Results: In the group with isolated oligohydramnios, there were significantly more Cesarean sections (p=0.0081) and more abnormal cardiotocographies (p=0.0005). Univariate and multivariate analyses showed that this difference was seen particularly in nulliparous women (p=0.0025 for Cesarean section and 0.0368 for abnormal cardiotocography). Peripartal and perinatal outcome parameters were not different between the two groups. Conclusion: In women with isolated oligohydramnios at term, there is no impact on fetal outcome. The influence of isolated oligohydramnios on the rate of cesarean section and abnormal cardiotocography is considered to be less than that of parity.